Parallel corpora. A real-time approach to the study of language change in progress - Christian Mair (Diacronia, 2015)
The paper draws data from four matching one-million word corpora, namely Brown (US, 1961), LOB (GB, 1961), Frown (US, 1992) and FLOB (GB, 1991), in order to provide an integrated description of synchronic (regional and stylistic) variation and short-term diachronic change in written Standard English. The analysis of a fairly large number of morphosyntactic variables shows that instances of direct structural change are rather rare in the period under review. Nevertheless there are numerous statistically significant diachronic developments which, taken together, provide evidence for a coherent discourse-pragmatic trend, the ‘colloquialisation’ of the norms of written English. This linguistic development is argued to be driven by a more general sociocultural trend, the shift of public taste towards greater informality.